Malaysian Siam Music in Northern Malaysia and Its Representation - Chayuti Tassanawongwara (IJCAS (International Journal of Creative and Arts Studies), 2017)
Some of the Thais were left behind in some parts of the land which once a Thailand’s territory. In the colonialism era, after Kelantan, Terangganu, Perlis and Kedah were annexed to Malaysia several decades ago by British, the Malaysian Siam who have chosen to stay put became the citizens of Malaysia despite being defined as Thais. The livelihood conditions of different nationalities are vital tools to distinguish one ethnic race from others. The first Malaysian Siam who ventured their way from South Thailand to settle in the land known as Melayu can be traced as far back as 300-500 years ago during the reign of King Boromma Trailokanat of Ayudhya era. There was an evidence of migration from then North Thailand downwards to the land of Melayu and inhabited at Sai Buri town. Today, the Malaysian Siams are densely populated across Kelantan, Perak, Perlis and Kedah. In this regard, it is a hard decision to choose the appropriate tools to represent the cultural identity. Music, in all possibilities, could be a likely solution to representation of cultural identity by importing them from its land of origin to reflect the unity of Thai people and the Malaysian Siam. Once the music is allowed to make its impact in protecting the identity of the Thai. This paper shall redound to the representation of Malaysian Siam in northern Malaysia, locally states of Perlis and Kedah, especially music in current use. The paper shall thoroughly present the result of analysis how the Malaysian Siam uses music to strengthen their cultural identity by the process of representation through a focusing on the theory of liminality.